Land Procurement for Public Utility Development in Mimika District, Papua Based on Law Number 2 of 2012 Regarding Land Procurement for Public Interest in The Autonomy Era - Eltinus Omaleng; Eriyantouw Wahid (Journal of Social Science, 2022)
The development of Papua must also be considered in developing Indonesia because it is a unity in the Bhineka Tunggal Ika series. So equality and justice in striving for the welfare of the people are also important for the people of Indonesia. Pancasila is the foundation of the Indonesian nation, which explains the five principles that have strong power in developing Indonesia towards a “Gotong Royong” society. The fifth precept of justice for all Indonesian people wants to show that this idea is Soekarno's idea of how the people enjoy the justice and welfare that is felt for the community both in the formal and non-formal fields which also leads to " cooperation". Then implement it in the Jokowi era which is to build and develop marginalized areas, from Sabang to Marouke, especially in marginalized and neglected areas. Land acquisition for development is the most complicated, namely if an agreement is not reached between the landowner and the constructing party, while the construction must be carried out. One solution that the government can choose is to complete development in a way that is acceptable to society. If all means cannot be implemented and development is urgently needed and the land cannot be moved, its location can be revoked as a final way, which must be regulated in law. Another most complicated problem is that in line with population growth and increasing dynamics of community aspirations, demands for development in the public interest are increasingly becoming. However, activities to meet these demands are faced with the increasingly limited availability of land and an underdeveloped land market. This has led to an uncontrolled increase in land prices, especially in urban areas. This condition also encourages land speculators to seek profit (rent-seeking) on every land transaction. The actions of land speculators often disrupt the smooth allocation of development requiring land, making it difficult to acquire land, especially for the development of public interests and creating a high-cost economy.